Manajemen Kurikulum Ismuba Berbasis Boarding School di SMA Muhammadiyah Wonosobo - Addinia Rizki Sabili; Hendro Widodo (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
The existence of formal schools under the auspices of bording school foundation has its own uniqueness compared to other schools in general. One of the models is Boarding School of Muhammadiyah Wonosobo High School. This article aims to describe in depth the Ismuba curriculum management based on Boarding School. This research type is field research naturally. This qualitative research departs from certain cases and conditions so isn’t use term population. Qualitative research uses the term social situation which consists of places, actors, activities that are integrated with each other. Data is collected by interviewing, documenting, and observing. The results of this research can be summarized as follows: (1) The management of